Development of an Ethnoscience-Based Science Encyclopedia Integrated with Role-Play Methods to Improve Elementary School Students’ Science Literacy - Siti Sangadah; Ana Fitrotun Nisa; Daimul Hasanah; Akbar Al Masjid; Suhailee Sohnui (CV. Creative Tugu Pena, 2026)
The rapid development of information and communication technology has influenced the field of education, which can be utilized in the learning process. This study aims to test the feasibility and effectiveness of developing an ethnoscience-based science encyclopedia integrated with role-playing methods to improve scientific literacy. This study is a research and development (R&D) study. The subjects of this study consisted of 67 fifth-grade elementary school students in Klaten Regency, Central Java, selected using purposive sampling techniques. Data collection techniques were through questionnaires, tests, and observations. Data were analyzed quantitatively and qualitatively, then analyzed inferentially with a paired sample t-test. The results of the study indicate that the development of an ethnoscience-based science encyclopedia integrated with role-playing methods is proven valid and effective in improving scientific literacy. The results of the study showed: (1) the validation of the science encyclopedia product obtained an average value of 97.22% from teaching material experts and 90.21% from material experts, and obtained a value of 95.5% from practitioners, and (2) the results of the analysis showed a probability value of 0.032 < 0.05, meaning that there was a difference between the results of the pretest of scientific literacy skills that had not been treated and the posttest that had implemented the science encyclopedia based on ethnoscience integrated with the role play method. Thus, the developed science encyclopedia was declared valid and effective in improving the science literacy skills of elementary school students.